What is a crime? : defining criminal conduct in contemporary society (Legal dimensions series., 2004)
"Drawing from diverse scholarly traditions - including law, sociology, cosmology and socio-legal studies - this collection of essays looks at the processes of defining crime and considers the varied and complex implications of our decisions to criminalize certain unwanted behaviour, from the perspective of various case studies the contributors reflect on the social processes that inform definitions of crime, criminal law, and its enforcement, while illuminating the subjective nature of crime and questioning the role of law in dealing with complex social issues." "What Is a Crime? will be of interest to a broad spectrum of readers with an interest in the governance of crime and its control in contemporary society. Students and scholars of law sociology, political science, philosophy and criminology will find this book invaluable in furthering the understanding of the processes of defining and responding to crime and criminal behaviour. It will also appeal to policymakers, criminal justice practitioners, and anyone with a stake in our current approaches to crime."--Jacket